Lunate excision with capitohamate fusion in the treatment of stage IIIB and IIIC Kienböck's disease - Mesut Tahta; Cem Ozcan; Gurkan Yildiz; Izge Gunal; Muhittin Sener (Acta Orthopaedica et Traumatologica Turcica, 2018)
Objective: The aim of this study was to report our results of lunate excision combined with capitohamate fusion in the treatment of Kienböck's stage IIIB/IIIC disease. Methods: A total of 7 patients with a mean age 35.2 (SD 11.5) years were enrolled in the study. Pain was the principal reason for surgery. All operations were carried out by the same senior surgeon. Patients were evaluated in terms of range of motion, DASH and VAS scores, satisfaction, and grip/tip/palmar/key pinch strength compared with contralateral sides. Preoperative carpal height indexes and findings of osteoarthritis were determined radiographically and compared with postoperative evaluations. Results: Mean duration of follow up was 15.2 months. Mean DASH and VAS scores were 13.8 2.7 and 2 1.1 respectively. The mean patient satisfaction score was 3.2 0.4 over 4 points. The mean grip strength in the operated hands was 66.4%, palmar pinch was 75.1%, tip pinch was 71.8% and key pinch was 70.4% when compared to the contralateral unaffected sides. The mean flexion range in the operated hands was 58.8%, extension range was 60.3%, radial deviation range was 65.2% and ulnar deviation range was 65.7% when compared to the contralateral sides. There was no significant difference between preoperative and postoperative carpal height ratios (p = 0.086). Conclusions: Our early term results indicate that lunate excision combined with capitohamate fusion may be an alternative treatment option in patients with stage IIIB and IIIC Kienböck's disease. Level of Evidence: Level IV, Therapeutic study. Keywords: Capitate bone, Excision, Fusion, Hamate, Kienböck's diseasse, Lunate bone